South Korea, China and the Road and Belt Initiative: economic and political factors - Barannikova, Anastasia (OrdnungsPolitisches Portal, 2021)
The present article addresses the problems of economic cooperation between China and ROK from the point of implementing their Eurasian integration initiatives - the One Belt, One Road, Eurasia Initiative and New Northern Policy. The initiatives of both countries, which at first glance are aimed at developing economies of the participants, also pursue distinct political goals. Accordingly, the most serious problems arising on the way of their implementation are of a political nature.
10419/233897
Keywords: Graue Literatur; Belt and Road Initiative; OBOR; Eurasia Initiative; Eurasian integration; China; ROK